Pengaruh Penerapan Media Pembelajaran E-Learning Berbasis Aplikasi Kahoot terhadap Keterampilan Menulis Bahasa Arab - Zakiyatul Abidah; M. Fathor Rohman; Yeni Rahmadian (Edu Journal Innovation in Learning and Education, 2023)
The purpose of this study is to determine the application of learning media and the influence of learning media on learning maharah al-kitabah (writing skills) Arabic type of guided writing. One of these learning media is by using Kahoot application-based E-learning, with this media students will feel more happy, excited and motivated when the Arabic learning process takes place. Researchers use quantitative research, a pre-experimental type. The population in this study was 105 learners. The instruments used are tests, observations, interviews, questionnaires and documentation. To find out whether there is an influence on the application of learning media, researchers analyze the data processed using t-tests and relative frequency distribution analysis techniques. The results of this research analysis are: 1) Researchers first create learning materials then researchers enter them in the kahoot application. Researchers get pins and links from the kahoot application, which are then shared with students in grades X-IPS 1. Students enter the kahoot application access and learning by opening the link that has been shared by the researcher. 2) Based on the results of the ujit calculation, the result is 12.999 and d.b is N-1=29-1=28. While the T-test table that uses one group refers to the level of significant numbers 0.05 which is 2.05 and 0.01 which is 2.76. Because the analysis results of the T-test calculation are higher than the level of significant values in the T-test table. Thus, the Working Hypothesis (Ha) is accepted and the Zero Hypothesis (Ho) is rejected. Furthermore, based on the calculation results using relative frequency distribution analysis techniques, it can be said that kahoot-based e-learning media learning media reached 70.166% and it included group 6